2009
DOI: 10.1007/s00464-009-0552-x
|View full text |Cite
|
Sign up to set email alerts
|

Is BMI greater than 60 kg/m2 a predictor of higher morbidity after laparoscopic Roux-en-Y gastric bypass?

Abstract: Patients with BMI >or= 60 kg/m(2) do not have a higher postoperative morbidity compared with other patients undergoing laparoscopic Roux-en-Y gastric bypass. The stricture rate is less in patients with BMI >or= 60 kg/m(2) compared with other patients. Longer follow-up is required to detect complications that occur after 1 year. Our study shows that laparoscopic Roux-en-Y gastric bypass can be safely performed on the super-supermorbidly obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…There was no higher complication index in surgeries for patients with a BMI≥60, coinciding with the report by Kushnir 44 . Bennet, in a study of mortality in bariatric surgery, found that mortality is related to age, and male sex, not nding a relationship with the increase in BMI as in our study 45 .…”
Section: Discussionsupporting
confidence: 90%
“…There was no higher complication index in surgeries for patients with a BMI≥60, coinciding with the report by Kushnir 44 . Bennet, in a study of mortality in bariatric surgery, found that mortality is related to age, and male sex, not nding a relationship with the increase in BMI as in our study 45 .…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the influence of pre-surgical weight on surgical morbidity is also uncertain. Retrospective recent studies, conducted in the maturity stage of laparoscopic surgery did not find that the evolution and morbidity related with IGB was different in super-obese patients (BMI > 60) compared to morbidly-obese patients with a BMI > 60 (34)(35)(36).…”
Section: Discussionmentioning
confidence: 88%
“…As stated in other similar studies (35), it is often difficult to achieve enough statistical power in these type of studies. Therefore, in order to achieve statistical significance in the postsurgical morbidity of group H, the sample size of the study should have been increased to 364 patients (182 patients in each arm), which can only be attainable in multicenter studies.…”
Section: Discussionmentioning
confidence: 92%
“…However, even US-based hospitals face a number of challenges when super-obese patients are admitted to the intensive-care unit. One report suggested that, among patients undergoing laparoscopic gastric operations, the rates of postoperative mortality and morbidity in patients with BMI values of >60 are not higher than those of patients with lower BMI values ( 11 ). However, there have been no reports concerning the mortality and morbidity rates of patients with BMI values of >80 (super-super-super obese); this degree of obesity might lead to severe disturbance of the microcirculation disturbance in the fatty tissue, which may be complicated by infection ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%